THE ROLE OF BATHORO KATONG IN SPREADING ISLAM IN PONOROGO - Mohammad Hafis (CV. Fahr Publishing, 2023)
The thesis entitled The Role of Bathoro Katong dalam Spreading Islam di Ponorogo has three focuses, namely: (1) the origin of Bathoro Katong, the figure of the spread of Islam in Ponorogo; (2) the role of Bathoro Katong in the spread of Islam in Ponorogo; and (3) the conditions before and after Islam entered Ponorogo. The method used in this study is with a literature approach (literatur review), this method is a research using library sources both from research results and books. In literature research, researchers do not have to go directly to the field, because the object of research is libraries (books), documents, archives, and so on. This study consists of four stages, namely: heuristics, verification / criticism of sources, interpretation, and writing history or historiography. From the results of this study, it was concluded that: (1) Bathoro Katong was the son of Brawijaya V from his wife, Princess Bagelan. (2) Bathoro Katong in Islamizing in Ponorogo assisted by Ki Ageng Mirah and Selo Aji, strtategi dahwah through cultural arts, education, marriage, politics and persuasive (while maintaining the value of old traditions). (3) Before Islam entered Ponorogo the community adhered to Hindu-Buddhist teachings, after the development of Islam, the old culture was adapted to Islamic norms. Keywords: Bathoro katong, Islam, Ponorogo